2015
DOI: 10.1007/s11936-015-0375-0
|View full text |Cite
|
Sign up to set email alerts
|

Statins in the Prevention of Contrast-Induced Nephropathy

Abstract: Coronary angiography and percutaneous coronary interventions are common procedures that utilize iodinated contrast medium to visualize the coronary arterial tree and treat stable and unstable ischemic heart syndromes. Exposure to contrast agents can cause acute and persistent worsening of renal function leading to increased morbidity and mortality. Certain patient characteristics such as age, presence of diabetes, congestive heart failure, chronic kidney disease, hemodynamic instability on presentation, and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 41 publications
0
23
0
9
Order By: Relevance
“…In this study, Iohexol (low-osmolar, non-ionic contrast medium) was also used to reduce complications and CIN incidence. Although, the exact pathophysiology of CIN remains unclear, the possible direct and indirect pathophysiologic effects of contrast exposure that have been suggested include renal vasoconstriction, which leads to decreased oxygenation of the medulla causing ischemia and renal injury, direct tubular toxicity due to the creation of oxygen free radicals, causing acute tubular necrosis, and a decrease in glomerular filtration due to the alterations of tubulo-glumeral regulatory mechanisms [4,8,20,21]. Nicorandil, a K-ATP channel opener and a NO donor, is currently used in the treatment of angina and acute heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Iohexol (low-osmolar, non-ionic contrast medium) was also used to reduce complications and CIN incidence. Although, the exact pathophysiology of CIN remains unclear, the possible direct and indirect pathophysiologic effects of contrast exposure that have been suggested include renal vasoconstriction, which leads to decreased oxygenation of the medulla causing ischemia and renal injury, direct tubular toxicity due to the creation of oxygen free radicals, causing acute tubular necrosis, and a decrease in glomerular filtration due to the alterations of tubulo-glumeral regulatory mechanisms [4,8,20,21]. Nicorandil, a K-ATP channel opener and a NO donor, is currently used in the treatment of angina and acute heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-induced nephropathy (CIN), also known as contrast-induced acute kidney injury (CI-AKI) is a well-known, prevalent and serious side effect of the administration of iodine contrast medium after angiocardiography or radiological procedures [1,2]. In clinical studies, CIN is defined as an elevation of serum creatinine level 44.2 µmol/L (0.5 mg/dL) or 25% above the baseline within 48-72 h after contrast administration without an alternative cause [3][4][5]. The exact pathophysiological mechanisms of CIN are complex and remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced age, diabetes, congestive heart failure, CKD, hemodynamic instability, and type and volume of contrast may all precipitate the development of CIN. [17] Previous research accentuated that adequate intravenous hydration with iso-osmolar crystalloids and limiting the amount of low-osmolar and iso-osmolar contrast are crucial for prevention of CIN. Several trials in various clinical conditions, including acute coronary syndromes, examined the effect of different types of statins, high-versus low-dose statins and loading versus chronic dosing of statins.…”
Section: Prevention Of Contrast-induced Nephropathy (Cin)mentioning
confidence: 99%
“…Advanced age, type and volume of contrast, pre-existing disease such as congestive heart failure and CKD, and haemodynamic instability are reportedly more likely to influence the development of CI-AKI. 11 Chyou et al 45 demonstrated that increased age, diabetes mellitus, acute coronary syndrome, and CKD are the factors responsible for precipitating the hazard for contrast-induced nephropathy. Further, Chung et al 46 confirmed that there is a 13% increased risk of developing severe renal failure with statin treatment among the highrisk population.…”
Section: Effect Of Underlying Diseases/risk Factors On Statin Efficacymentioning
confidence: 99%